Study on Characteristics of the Water-Sediment Two-Phase Flow in Fractures Based on Numerical Simulation. (6th May 2022) - Cao, Lili; Wu, Chuan; Xu, Hanhua; Yu, Hao; Li, Ming; Han, Yu; Chen, Zhanqing
Abstract : The instability of water-sediment flow in fractures can easily induce water-sediment disasters. Therefore, it is of great significance for the prevention and control of water-sediment inrush to study the water-sediment two-phase flow in fractures. Based on the water-sediment two-phase flow theory, a model of the water-sediment two-phase flow system was established. The Ansys Fluent software was used to study the characteristics of the water-sediment two-phase flow in smooth and rough fractures. The spatial-temporal evolution laws of the water-sediment two-phase flow were studied; the results indicated that they did not change with time in the smooth fractured flow fields, while changing continuously with time in the rough fractured flow fields and in a dynamic steady state. The research results can provide references for the water-sediment two-phase flow in fractures and rock mass.